Consumer choice and local network effects in mobile telecommunications in Turkey - Mehmet Karaçuka; A. Nazif Çatik; Justus Haucap (Heinrich Heine University Düsseldorf, Düsseldorf Institute for Competition Economics (DICE), 2012)
Turkish consumer survey data is used to analyze the main factors that affect consumers' choice of different mobile telecommunications networks. The analysis shows that consumers' choice is significantly affected by the choices of other consumers with whom the consumer is more likely to interact. The results show that local network effects exist and consumer characteristics have significant effects on consumer choice. This finding means that consumers are more likely to be affected by the choices of other people within their local area than by the overall size of a network. The results also suggest that local effects may outweigh macro network effects at least in Turkey.
Keywords: C23; L13; L9; 330; mobile telecommunications; network effects; discrete choice analysis; Mobilkommunikation; Netzeffekt; Konsumentenverhalten; Region; Diskrete Entscheidung; Schätzung; Türkei